Diskursus Problematika Wanprestasi Terhadap Pembatalan Perjanjian Pengikatan Jual Beli (PPJB) Lahan di Bakauheni Kalianda (Studi Kasus Putusan Nomor 75/Pdt.G/2022/PN.Tgr) - Eranda, Genta; Hartono, Rudi (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
The cruciality of the implementation of the Land Sale and Purchase Agreement (PPJB) often raises the issue of default, so that in the midst of running the repayment payment must be canceled, and the creditor in this case must return the full amount of money plus moratoir interest jointly and severally as the contents of the agreement. As in Decision Number 75/Pdt.G/2022/PN.Tgr in which Hutama Karya (Persero) against Drs. Iskandar Zulkarnaen (PT Sanitarindo Tangsel Jaya), the defendant was declared negligent in not returning the payment of IDR 205,148,825,000, where the payment obligation by PT Sanitarindo Tangsel Jaya arose from PPJB Number: X/002/Perj./STJ/HK/X/2021 dated October 29, 2021 and Deed of Addendum I. This research uses a normative approach. This research method uses a normative approach that refers to the applicable laws and regulations accompanied by literature studies in the form of books, journals, and other literature that supports this research. Analysis of jurisprudence uses qualitative descriptive to describe legal phenomena to be later concluded from general statements to specific conclusions. The results showed that PT Sanitarindo Tangsel Jaya is obliged to return all the money to Hutama Karya (Persero) for the purchase of the land in the amount of Rp. 205,148,825,000. PT Sanitarindo Tangsel Jaya must pay off the payment no later than 6 (six) months from the date of signing the Agreement, but until the case is heard it does not carry out its obligations. Because it was not agreed by the litigants, the interest determined by law, which although set at 6% per year The consequences incurred are material losses from the remaining losses due to default, namely in the form of debt accommodation for the return of advances that have not been returned by the seller / defendant to the buyer / Hutama Karya (Persero) other costs, which can be in the form of accommodation of costs incurred during the management of the case concerned. Paying immaterial court costs can be in the form of psychological losses to Hutama Karya (Persero) or the buyer due to the defendant's default.Keywords: Decision, Default, Land, PPJB